Screening for potential novel probiotic Levilactobacillus brevis RAMULAB52 with antihyperglycemic property from fermented Carica papaya L. - Sreepathi, Navya; Kumari, V. B. Chandana; Huligere, Sujay S.; Al-Odayni, Abdel-Basit; Lasehinde, Victor; Jayanthi, M. K.; Ramu, Ramith (Frontiers in Microbiology, 2023)
Probiotics are live microorganisms, intended to have multiple health benefits when administered in an appropriate amount. Fermented foods are the primary source of these organisms. The LAB (lactic acid bacteria) isolated from fermented papaya (Carica papaya L.) were examined for their potential probiotic activity by in vitro methods. Based on the morphological, physiological, fermentative, and biochemical properties, the isolated strains were Gram-positive, catalase-negative, and carbohydrate fermenting. The isolated LAB strain was resistant to acid bile (0.3 & 1%), phenol (0.1 & 0.4%), and simulated gastrointestinal juice (pH 3-8), and expressed potent antibacterial, and antioxidant abilities. They also showed resistance to kanamycin, vancomycin, and methicillin along with an appreciable rate of autoaggregation (83%). The isolate expressed adhesion with chicken crop epithelial cells, buccal epithelial cells, and HT-29 cells. The safety assessments, including the hemolytic assay and DNase activity, showed no evidence of hemolysis or DNA degradation, indicating that the LAB isolate is safe and 16s rRNA sequence is used to validate the isolate. The isolate's antidiabetic activity was assessed through the inhibition of α-amylase and α-glucosidase, resulting in 86.97% and 75.87% inhibition, respectively. The inhibition of target enzymes has also been analyzed by in silico studies using docking and MD simulation for the extracted (LC-MS) organic acids. Hydroxycitric acid was found to interact with key amino acid residues of α-amylase (GLU233 and ASP197) and α-glucosidase (ASN241, ARG312, GLU304, SER308, HIS279, PRO309, and PHE311) via hydrogen bond formation, among the organic acids obtained. In this study, the results obtained prove that the LAB strain Levilactobacillus brevis RAMULAB52 isolated from fermented papaya possesses promising probiotic properties and can be used as an effective remedy for diabetes.